Chlorophyll as a biomarker for early disease diagnosis. (9th May 2018) - Atta, Babar Manzoor; Saleem, M; Ali, Hina; Arshad, Hafiz Muhammad Imran; Ahmed, M
Abstract: The current study was designed to identify the stage for the diagnosis of disease before visible symptoms appeared. Fluorescence spectroscopy has been employed to identify disease signatures for its early diagnosis in rice plant leaves. Bacterial leaf blight (BLB) diseased and healthy leaf samples were collected from the rice fields in September, 2017 which were then used to record spectra using an excitation wavelength at 410 nm. The spectral range of emission was set from 420 to 800 nm which covers the blue–green and the chlorophyll bands. It was found that diseased leaves have a narrower 'chlorophyll a' band than healthy ones, and furthermore, that the emission band at 730 nm was either declined or depleted in the sample with high infection symptoms. In contrast, the blue–green region was observed to increase due to the emergence of disease. As the band intensity of chlorophyll decreases during infection, this decrease in chlorophyll content and increase in the blue–green spectral region could provide a new approach for predicting BLB at an early stage. The important finding was that the chlorophyll degradation and rise in the blue–green region take place in leaves with BLB or during BLB infection. Principal component analysis has been applied to spectral data which successfully separated diseased samples from healthy ones even with very small spectral variations.